Retained intravitreal lens fragments after phacoemulsification: a clinicopathological correlation. Issue 10 (1st October 1999) - Yeo, L M W; Charteris, D G; Bunce, C; Luthert, P J; Gregor, Z J
Abstract : AIMS: To explore the relation between clinical course and timing of vitrectomy with the nature and intensity of intraocular inflammatory response in eyes with retained intravitreal lens fragments following complicated phacoemulsification. METHODS: Prospective evaluation of 22 eyes with retained lens fragments with emphasis on corneal clarity, uveitis, intraocular pressure (IOP), timing of vitrectomy, and visual outcome. Numbers of different types of inflammatory cells in vitreous washings were counted, masked to clinical details, in three non-overlapping adjacent high power fields. Relations between clinical and pathological findings were assessed. RESULTS: The IOP was raised in 19 eyes before vitrectomy and remained high in nine postoperatively. The latter had higher median total cell count (104 cells/mm 2 ) than those with normal postoperative IOP (37 cells/mm 2 ) but this difference was not statistically significantly different (p=0.17). Nine of 22 eyes underwent vitrectomy within 1 week of cataract surgery. Median total cell count in these eyes was 20 cells/mm 2 compared with 140 cells/mm 2 in eyes vitrectomised later—this difference was statistically significant (p <0.001). Final visual acuity was 6/12 or better in 13 eyes, these had fewer intravitreal inflammatory cells than the remaining six with poor visual outcome and no pre-existing cause for this (three patients excluded) (p=0.02). Macrophages were the predominant inflammatory cell type. CONCLUSION: There was significantly less inflammatory cell activity in eyes which had retained lens fragments removed early (within 1 week). Later removal was associated with persistently elevated IOP and poorer visual outcome.